Interferon Alpha Characterization and Its Comparative Expression in PBM Cells of Capra hircus and Antelope cervicapra Cultured in the Presence of TLR9 Agonist. (9th June 2010) - Doreswamy, Ramesh; Saini, Mohini; Swarup, Devendra; Singh, Vivek Kumar; Upreti, Suchitra; Das, Asit; Gupta, Praveen K.
Abstract : TLR9 plays pivotal role in innate immune responses through upregulation of costimulatory molecules and induction of proinflammatory cytokines like type I interferons including interferon alpha (IFNA). The present study characterized IFNA cDNA and predicted protein sequences in goat and black buck. Response of the PBM cells to TLR9 agonist CpG ODN C and Phorbol Myristate Acetate (PMA) was evaluated by realtime PCR. IFNA coding sequences were amplified from leukocyte cDNA and cloned in pGEMT-easy vector for nucleotide sequencing. Sequence analysis revealed 570 bp, IFNA ORF encoding 189 amino acids in goat and black buck. Black buck and goat IFNA has 92.1% to 94.7% and 93% to 95.6% similarity at nucleotide level, 86.3% to 89.5% and 70.9% to 91.6% identity at amino acid level with other ruminants, respectively. Nonsynonymous substitutions exceeding synonymous substitutions indicated IFNA evolved through positive selection among ruminants. In spite of lower total leukocyte count, the innate immune cells like monocytes and neutrophils were more in black buck compared to goat. In addition, CpG ODN C-stimulated PBM cells revealed raised IFNA transcript in black buck than goat. These findings indicate sturdy genetically governed immune system in wild antelope black buck compared to domestic ruminant goat.